Parental age and risk of depression: A nationwide, population-based case-control study - Filatova Svetlana; Upadhyaya Subina; Luntamo Terhi; Sourander Andre; Chudal Roshan (Netherlands, 2022)
Background: The global prevalence of depression has increased in recent decades and so has the average age of parenthood. Younger and older parental age have been associated with several mental disorders in their offspring, but the associations for depression have been inconsistent.
Methods: This study comprised 37,682 singleton births in Finland from 1987- 2007. The subjects were living in Finland at the end of 2012 and had a depressive disorder recorded in the Care Register for Health Care. We also randomly identified 148,795 controls from the Population Register. When missing obsevations excluded the sample was Ncases=18,708 and Ncontrols=77,243. The results were adjusted for the parents' psychiatric history, depression history, marital status and place of birth, the mothers' maternal socioeconomic status, smoking during pregnancy and previous births and the children's birth weight.
Results: We found a U-shaped association between offspring depression and the age of both parents. The highest odds of depression occurred when the fathers were aged 50 plus years (adjusted Odds Ratio (ORa) 1.51, 95% CI 1.23-1.86) and the mothers were under 20 (ORa 1.44, 95% CI 1.29-1.60) compared to the reference category of parents aged 25-29 years.
Limitations: The study was limited to depression diagnosed by specialised health care services and had a relatively short follow-up period. Some data were missing and that could lead to risk estimation biases.
Conclusion: Diagnosed depression was higher among the offspring of younger and older parents. The results suggest that the age of the parent is etiologically associated with offspring depression.
Keywords: Maternal age; Offspring depression; Parental age; Paternal age.